Prediction of thermal skin burn based on the combined mathematical model of the skin and clothing. Issue 12 (2nd December 2018) - Fu, Ming; Chen, Weiwang; Weng, Wenguo; Yuan, Mengqi; Luo, Na; Xu, Xiaoyu
Abstract: As the result of exposed to thermal radiation and fire exposure, skin burn or even worse injuries are very common for building occupants and fire fighters. To accurately predict their skin temperature and burn situation, an assessment method of the mathematical model is developed for various thermal radiation conditions. The combined mathematical model includes the heat and moisture transfer within the skin and clothing systems. It is validated with a good agreement with the previous experimental study. The effects of thermal radiation, air gap and moisture transfer on burn prediction were also studied. The results showed that the time to the second degree burn is affected by the heat flux level, gap size and moisture location. It is expected that the developed method can be used to evaluate the thermal protective performance of protective clothing during exposure to thermal hazards and provide appropriate information to clinical observation and decision-making for skin thermal injuries.